A Review on Atmospheric Analysis Focusing on Public Health, Environmental Legislation and Chemical Characterization. (7th November 2022) - Gioda, Adriana; Beringui, Karmel; Justo, Elizanne P. S.; Ventura, Luciana M. B.; Massone, Carlos G.; Costa, Silvânio Silvério Lopes; Oliveira, Sidimar Santos; Araujo, Rennan Geovanny Oliveira; Nascimento, Nivia de M.; Severino, Hemmely Guilhermond S.; Duyck, Christiane B.; de Souza, Jefferson Rodrigues; et al.
Abstract: Atmospheric pollution has been considered one of the most important topics in environmental science once it can be related to the incidence of respiratory diseases, climate change, and others. Knowing the composition of this complex and variable mixture of gases and particulate matter is crucial to understand the damages it causes, help establish limit levels, reduce emissions, and mitigate risks. In this work, the current scenario of the legislation and guideline values for indoor and outdoor atmospheric parameters will be reviewed, focusing on the inorganic and organic compositions of particulate matter and on biomonitoring. Considering the concentration level of the contaminants in air and the physical aspects (meteorological conditions) involved in the dispersion of these contaminants, different approaches for air sampling and analysis have been developed in recent years. Finally, this review presents the importance of data analysis, whose main objective is to transform analytical results into reliable information about the significance of anthropic activities in air pollution and its possible sources. This information is a useful tool to help the government implement actions against atmospheric air pollution.